Renal Insufficiency and Early Bystander CPR Predict In-Hospital Outcomes in Cardiac Arrest Patients Undergoing Mild Therapeutic Hypothermia and Cardiac Catheterization: Return of Spontaneous Circulation, Cooling, and Catheterization Registry (ROSCCC Registry). (18th January 2016) - Chelvanathan, Anjala; Allen, David; Bews, Hilary; Ducas, John; Minhas, Kunal; Vo, Minh; Kass, Malek; Ravandi, Amir; Tam, James W.; Jassal, Davinder S.; Hussain, Farrukh
Abstract : Objective. Out of hospital cardiac arrest (OHCA) patients are a critically ill patient population with high mortality. Combining mild therapeutic hypothermia (MTH) with early coronary intervention may improve outcomes in this population. The aim of this study was to evaluate predictors of mortality in OHCA patients undergoing MTH with and without cardiac catheterization. Design. A retrospective cohort of OHCA patients who underwent MTH with catheterization (MTH + C) and without catheterization (MTH + NC) between 2006 and 2011 was analyzed at a single tertiary care centre. Predictors of in-hospital mortality and neurologic outcome were determined. Results. The study population included 176 patients who underwent MTH for OHCA. A total of 66 patients underwent cardiac catheterization (MTH + C) and 110 patients did not undergo cardiac catheterization (MTH + NC). Immediate bystander CPR occurred in approximately half of the total population. In the MTH + C and MTH + NC groups, the in-hospital mortality was 48% and 78%, respectively. The only independent predictor of in-hospital mortality for patients with MTH + C, after multivariate analysis, was baseline renal insufficiency (OR = 8.2, 95% CI 1.8–47.1, and p = 0.009). Conclusion. Despite early cardiac catheterization, renal insufficiency and the absence of immediate CPR are potent predictors of death and poor neurologic outcome in patients with OHCA.